Active visual inhibition is preserved in the presence of a distracter: A cross-cultural, ageing and dementia study. (September 2021) - Polden, Megan; Crawford, Trevor J.
Abstract: The current study investigated a novel visual distracter task as a potential diagnostic marker for the detection of cognitive impairment and the extent to which this compares in healthy ageing across two cultures. The Inhibition of a Recent Distracter Effect (IRD) refers to the inhibition of a saccadic eye movement towards a target that is presented at the location of a previous distracter. Two studies compared the IRD across a large cross-cultural sample comprising of young (N = 75), old European participants (N = 119), old south Asian participants (N = 83), participants with Dementia due to Alzheimer's disease (N = 65) and Mild cognitive impairment (N = 91). Significantly longer saccadic reaction times on the target to distracter trials, in comparison to the target to target trials were evident in all groups and age cohorts. Importantly, the IRD was also preserved in participants with Alzheimer's Disease and mild cognitive impairment demonstrating that the IRD is robust across cultures, age groups and clinical populations. Eye-tracking is increasingly used as a dual diagnostic and experimental probe for the investigation of cognitive control in Alzheimer's disease. As a promising methodology for the early diagnosis of dementia, it is important to understand the cognitive operations in relation to eye-tracking that are well preserved as well as those that are abnormal. Paradigms should also be validated across ethnicity/culture, clinical groups and age cohorts.